1975
DOI: 10.1111/j.1600-0765.1975.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial gingivitis in dogs

Abstract: The gingival characteristics after four days of gingivitis development have been studied in three Beagle dogs. Gingival normality was induced by regular tooth cleaning and gingivitis was provoked by abolishing oral hygiene procedures and giving the animals a soft diet. Measurements of the gingival fluid flow and the amount of crevicular leukocytes served to clinically assess the gingival condition. Semi‐ and ultra‐thin sections from contralateral biopsies of buccal gingival tissues from premolars obtained on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 15 publications
(9 reference statements)
2
33
0
Order By: Relevance
“…He suggests that this may be a pointless pursuit, mainly since even non-keratinized epithelia may offer resistance to the penetration of many substances (35,38) and 41 (1983) since keratinization of the highly permeable (28,30) junctional epithelium may lead to loss of epithelial attachment to the tooth surface and thus be harmful. Although this latter point may be well taken, it should be kept in mind that in spite of the intensive antibacterial therapy over considerable periods of time in this and other (2, 5 , 32) studies, keratinization of the junctional epithelium in situ has never been reported as a result of antibacterial therapy and may not be readily achieved (30,41).…”
Section: Discussionmentioning
confidence: 95%
“…He suggests that this may be a pointless pursuit, mainly since even non-keratinized epithelia may offer resistance to the penetration of many substances (35,38) and 41 (1983) since keratinization of the highly permeable (28,30) junctional epithelium may lead to loss of epithelial attachment to the tooth surface and thus be harmful. Although this latter point may be well taken, it should be kept in mind that in spite of the intensive antibacterial therapy over considerable periods of time in this and other (2, 5 , 32) studies, keratinization of the junctional epithelium in situ has never been reported as a result of antibacterial therapy and may not be readily achieved (30,41).…”
Section: Discussionmentioning
confidence: 95%
“…In inflammatory gingivae, numerous neutrophils and macrophages emigrate into the JE, with increasing signs of inflammation; these cells eventually become the predominant population (Schroeder et al, 1975). The activity of various proteinases (cathepsins B, D, H, and L, collagenase, and elastase) has been shown to increase with the severity of periodontitis (Ishikawa et al, 1972;Kunimatsu et al, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Capillary luminal distances (VD in our study) probably decrease and sometimes are completely occluded in DM because of structural alterations in vessel walls. A tendency for vascular thickening secondary to atherosclerotic changes with occlusion of small vessels is regarded as one of the putative factors in luminal distance decrease 16,58,59 . Gül and Özsoy, 60 in an experimental study in rats, examined the thickening of gingival vessels in detail by transmission electron microscopy, and they observed that the lumens had been closed by epithelial cells proliferation in some sections.…”
Section: Discussionmentioning
confidence: 99%